Social visual engagement in infants and toddlers with autism: Early developmental transitions and a model of pathogenesis. (March 2015) - Klin, Ami; Shultz, Sarah; Jones, Warren
Highlights: Abnormalities in perception of biological motion and eye looking are core aspects of autism. Decline in eye looking in infants later diagnosed with autism is a candidate endophenotype. Visual imprinting in chick is a model for gene–brain–behavior studies of eye looking in autism. A model of autism pathogenesis implicates neurodevelopmental transitions in early infancy. Abstract: Efforts to determine and understand the causes of autism are currently hampered by a large disconnect between recent molecular genetics findings that are associated with the condition and the core behavioral symptoms that define the condition. In this perspective piece, we propose a systems biology framework to bridge that gap between genes and symptoms. The framework focuses on basic mechanisms of socialization that are highly-conserved in evolution and are early-emerging in development. By conceiving of these basic mechanisms of socialization as quantitative endophenotypes, we hope to connect genes and behavior in autism through integrative studies of neurodevelopmental, behavioral, and epigenetic changes. These changes both lead to and are led by the accomplishment of specific social adaptive tasks in a typical infant's life. However, based on recent research that indicates that infants later diagnosed with autism fail to accomplish at least some of these tasks, we suggest that a narrow developmental period, spanning critical transitions from reflexive, subcortically-controlled visual behavior to interactional, cortically-controlled and social visual behavior be prioritized for future study. Mapping epigenetic, neural, and behavioral changes that both drive and are driven by these early transitions may shed a bright light on the pathogenesis of autism.